Peningkatan Kandungan Protein Mie Basah dari Tapioka dengan Substitusi Tepung Koro Pedang Putih (Canavalia ensiformis L.) - Agnes Murdiati; Sri Anggrahini; Ayuk Alim (agriTECH, 2015)
Noodle can be made from tapioca, but the protein content was very limited. The purpose of this study was to increase protein content of tapioca wet noodle with addition of 0-50% white jack bean flour and to evaluate the physical, chemical and organoleptic properties. This study was preceded by a reduction HCN content. After HCN content fulfilled SNI standards, white jack bean was then made into flour. In this study, wet noodle was made with the ratio of tapioca: white jack bean flour 100:0; 90:10; 80:20; 70:30; 60:40; and 50:50 respectively. Physical characteristics of noodle was investigated in this study were cooking loss, expansion ratio, tensile strength, and elongation. Organoleptic characteristics were studied by preference and difference test.  Noodle product which was preferred by panelists was analyzed for the nutritional content. The results showed that soaking jack bean in 2% sodium bicarbonate solution for 40 hours with pulping in the first 10 hours and continued with soaking water 3 times 10 hours can reduce HCN content by 87.08%. The cooking loss and force of tensile strength were increased while expansion ratio and elongation decreased with higher proportions of white jack bean flour used. Wet mie made of ratio tapioca: white jack bean flour 80:20 got the preferences by panelists, and was able to increase protein content 9.51 fold with protein content 7.15% db.ABSTRAKMie dapat dibuat dari tapioka, namun kandungan protein mie tapioka sangat rendah. Tujuan dari penelitian ini adalah untuk meningkatkan kandungan protein mie basah dari tapioka dengan penambahan tepung koro pedang putih 0-50% dan evaluasi sifat fisik, kimia, dan organoleptik produk mie basah tersebut. Penelitian ini didahului dengan pengurangan kadar HCN koro pedang putih dan pembuatan tepung koro pedang putih. Pembuatan mie basah dari tapioka dilakukan dengan variasi rasio campuran tapioka: tepung koro pedang putih 100:0; 90:10; 80:20; 70:30; 60:40; dan 50:50. Karakteristik fisik mie yang diteliti meliputi kehilangan padatan akibat pemasakan, rasio pengembangan, tensile strength, dan elongasi. Karakteristik organoleptik mie yang diteliti meliputi uji kesukaan dan pembedaan. Mie yang disukai panelis selanjutnya dianalisis kandungan gizinya. Hasil penelitian menunjukkan bahwa perendaman koro pedang putih dalam larutan natrium bikarbonat 2% selama 40 jam dengan pengupasan pada jam ke-10 pertama dan dilanjutkan dengan penggantian air rendaman setiap 10 jam dapat mengurangi kadar HCN sebesar 87,08%. Pada mie yang dihasilkan, makin banyak penambahan tepung koro pedang putih, kehilangan padatan akibat pemasakan (cooking loss) dan gaya pada tensile strength meningkat, sedangkan rasio pengembangan dan elongasi menurun. Produk mie basah yang dibuat dengan rasio tapioka: tepung koro pedang putih sebanyak 80:20 masih disukai panelis, dan mampu meningkatkan kandungan protein sebesar 9,51 kali sehingga kandungan protein mie yang dihasilkan sebanyak 7,15% db.